(untitled) (Revista da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo, 1974)
Six rams of the “Crioula” breed were divided ,at random, in 2 groups and submitted to scrotal insulation during 4 and 8 days respectively. During 9 months, 180 semen collections were made by electric shocks. Research was conducted on semen volume, semen microscopic waves, motility of spermatozoa, seminal pH, concentration and changes in the morphology of the sperm cells through the Williams stain and formol saline methods, and histologic alterations in the testicles. Analysis of data revealed that frequency of ejaculations did not interfere in semen quality and semen volume was not affected by scrotal insulation. On the other hand, the semen picture was disturbed in microscopic waves, motility, pH, concentration and by increasing of morphologically abnormal spermatozoa. Histologic alterations in the testicles were the more accentuated the longer was the period of scrotal insulation. Regeneration of these characteristics took place at different intervals of time up to 3 months after experimental scrotal insulation.